Pemberdayaan Sungai Guna Mendukung Ketersediaan Pangan di Pesantren Darul Mukhlasin Pekanbaru - Mufti Mufti; Niken Nurwanti; Dedi Zargustin (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Food sufficiency is a condition that is expected by every human individual. Food sufficiency, both in terms of quality and quantity, needs to be pursued. One way to fulfill food sufficiency is to empower existing resources. The Food Security Agency through the Center for Consumption Diversification and Food Safety has re-launched the Sustainable Food House Area Concept (KRPL), in order to accelerate food diversification and strengthen community food security. Darul Mukhlasin Islamic Boarding School, also known as the Al-Qur'an and Natural Da'wah Vocational High School (SMK ADA) is one of the Islamic boarding schools located in Pekanbaru City. This pesantren is located in Rumbai Bukit Village, Rumbai District, Pekanbaru City, and has 102 students. In the area of ??the Islamic boarding school, there is a river that is partially unused. The results of the evaluation of the implementation of community service activities regarding river empowerment were concluded as follows: Knowledge of aquatic resource empowerment and catfish cultivation increased by 88.00%, with very good criteria. Suggestions for further service activities need to increase knowledge and skills with different materials, for example about integrated farming, considering that there is still quite a large area around the Darul Mukhlasin Islamic Boarding School, Rumbai Bukit Village, Rumbai Barat District, Pekanbaru City.